Does trade reduce poverty? A view from Africa - Maëlan Le Goff; Raju Jan Singh (Journal of African Trade, 2014)
Although trade liberalization is being actively promoted as a key component in development strategies, theoretically, the impact of trade openness on poverty reduction is ambiguous. On the one hand, a more liberalized trade regime is argued to change relative factor prices in favor of the more abundant factor. If poverty and relative low income stem from abundance of labor, greater trade openness should lead to higher labor prices and a decrease in poverty. However, should the re-allocation of factors be hampered, the expected benefits from freer trade may not materialize. The theoretical ambiguity on the effects of openness regarding the trade-poverty relationship is also apparent in the empirical literature. To resolve this ambiguity, this paper examines whether the effect of openness on poverty varies with some country characteristics. Using a panel of African countries over the period 1981-2010 and testing for non-linearities in the trade-poverty relationship, we find that trade openness tends to reduce poverty in countries where financial sectors are deep, education levels high and institutions strong.
Keywords: F02; F15; O11; O55; 330; Trade; Poverty; Africa